The Power of Storytelling and Digital Storytelling in Teaching Polish to Learners in UK - Hrycak-Krzyżanowska, Dorota (Ludicity in (Glotto)Didactic, 2020)
Using stories for educational purposes is an effective teaching strategy especially for teaching languages. Most learners enjoy listening to stories. Stories have a power, which can bring students into a world of imagination and draw a colourful picture with interesting characters. Storytelling is one of the most useful techniques to attract students in the learning process effectively. Telling stories provides learners with an opportunity to discover experiences of real life and the language learning together. Storytelling is a teaching method which can help young learners to acquire knowledge, literacy, imagination, creativity and critical thinking. Therefore, storytelling would be very useful in teaching the Polish language in UK.